Reducing the torsional behavior in irregular special moment resisting frames with steel dampers - Billy Fernandus; I Putu Ellsa Sarassantika (Journal of Infrastructure Planning and Engineering, 2022)
Torsional behavior occurs during the earthquake and it caused displacement on the structure. This study evaluated the used of the metallic damper to the asymmetric three-story building structure in various ground motions scaled to response spectrum. Significant strength and stiffness enhancements were achieved in structure incorporate with damper. Seismic performance evaluation revealed that the used of the damper can reduce lateral displacement approximately 57-65%. The damper could dissipate the energy 28-36%. The use of the damper effectively justified proposed method applicability to seismic structural design.